2020
DOI: 10.1002/ajmg.a.61614
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloepimetaphyseal dysplasia with elevated plasma lysosomal enzymes caused by homozygous variant in MBTPS1

Abstract: Variants in MBTPS1 (membrane-bound transcription factor peptidase, site 1) encoding the protein convertase site-1 protease (S1P) were recently reported in a single individual with skeletal dysplasia and elevated plasma lysosomal enzymes. Here, we report the second individual with this newly described autosomal recessive spondyloepiphyseal dysplasia (OMIM #618392), presenting severe growth retardation, cataract and dysmorphic features, mainly retromicrognathia. Epilepsy and craniosynostosis were novel findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Previous studies have shown that S1P is essential for lysosomal biogenesis (Carvalho et al , 2020), and abnormal lysosomes were consistently found in patients (Fig EV2A, lower panel). Lipid deposition was observed in the patient’s skin lesions, as evidenced by increased cytoplasmic lipid droplets (Fig EV2A, lower panel).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Previous studies have shown that S1P is essential for lysosomal biogenesis (Carvalho et al , 2020), and abnormal lysosomes were consistently found in patients (Fig EV2A, lower panel). Lipid deposition was observed in the patient’s skin lesions, as evidenced by increased cytoplasmic lipid droplets (Fig EV2A, lower panel).…”
Section: Resultssupporting
confidence: 51%
“…A significant increase in the number of mitochondria (161.5% increase) and morphological abnormalities in the mitochondria (100.7% increase in the length and 10.3% decrease in the length-towidth ratio) were observed in the skin lesions of patient 1 by Previous studies have shown that S1P is essential for lysosomal biogenesis (Carvalho et al, 2020), and abnormal lysosomes were consistently found in patients (Fig EV2A,lower panel). Lipid deposition was observed in the patient's skin lesions, as evidenced by increased cytoplasmic lipid droplets (Fig EV2A,lower panel).…”
Section: S1p Deficiency Causes Abnormal Mitochondrial Morphology and ...mentioning
confidence: 69%
See 1 more Smart Citation
“…A phenotype substantially different from the case has been reported by Kondo et al [ 3 ] and our proband. Another case of Kondo-Fu type spondyloepiphyseal dysplasia (SEDKF) was reported with unique findings in a 5-year-old Brazilian girl with epilepsy and craniosynostosis [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only three patients have been reported to carry the MBTPS1 variants. The affected individuals had similar clinical manifestations, presenting severely growth retardation, dysmorphic facial features including large ears, prominent forehead and cheekbones, skeletal dysplasia and cataract ( 1 3 ). Besides, epilepsy, craniosynostosis and hernia were reported in different individuals.…”
Section: Introductionmentioning
confidence: 99%